Upaya Peningkatan Keaktifan Siswa melalui Metode Talking Stick pada Siswa Kelas III SDN Karanggedang - Inas Rafida; Sugeng Eko Putro Widoyoko; Titi Anjarini (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to determine whether the use of the talking stick learning model can increase student activity in the third grade thematic learning at SDN Karanggedang. The design used in this research is classroom action research which is carried out in two cycles. The results of research observations carried out showed an increase from cycle to cycle. Active learning in the first cycle got 58.45% in the less active category, in the second cycle it increased by 26.05%, which amounted to 84.5% in the very active category. The achievement for the implementation of learning by applying the talking stick model in the first cycle was 73% with a good category and in the second cycle it got 88.45% with a very good category, the achievement of student activity using the talking stick model is considered successful in reaching the limit of activity given, which is 80%.